The Art and Craft of Bricolage in Evaluation - Aston, Thomas; Apgar, Marina (CDI Practice Paper, 2022)
This CDI Practice Paper by Tom Aston and Marina Apgar makes the case for ‘bricolage’ in complexity-aware and qualitative evaluation methods. It provides a framework based on a review of 33 methods to support evaluators to be more intentional about bricolage and to combine the component parts of relevant methods more effectively. It discusses two cases from practice to illustrate the value added of taking a more intentional approach. It further argues that navigating different forms of power is a critical skill for bricolage, and that doing so can help to ensure rigour.

Innovating for inclusive rigour in peacebuilding evaluation - Apgar, Marina; Báez-Silva, Ángela Maria; Deng, Ayak Chol; Fairey, Tiffany; Rohrbach, Livia; Alamoussa, Dioma; Bradburn, Helene; Cubillos, Edwin; Gray, Stephen; Wingender, Leslie (Institute of Development Studies, 2022)
Inclusive and rigorous peacebuilding evaluation is both vital and complex. In this blog we share examples of how we are innovating our methodologies to move towards participatory and adaptive practice.